Trabalho e cotidiano do assistente social: desvendando um campo de mediações éticas na defesa dos direitos humanos - Moraes, Josiane (2013)
This thesis discusses and deepens reflection about professional ethical exercise of the Social Worker in defense of human rights expressed in the Code of Ethics of 1993 in the perspective of Ethical-Political Project of Social Work. The analytical framework woven throughout the four chapters that constitute this work is result of a profound dialogue with Marxist theoretical framework and the research subjects, given that we chose a qualitative methodology and, from the narratives brought by Social Workers we dived into daily work and apprehended the meanings of ethical exercise. The subjects who participated in the interviews (collective and individual) were intentionally chosen, constituting a universe of six interlocutors with densely lived experiences of teaching disciplines about ethics, social protection, public policies, and also human rights activism. Thereby, chapter I presents the theoretical underpinnings that guided our study and the construction methodology for the field action. In Chapter II, we contextualise the socio-historical formation of Brazil, as well as the trajectory of Social Work from 1970 to 1990, questioning the construction of new Social Work professional project. Finally, Chapters III and IV, deepens reflection on the daily life of Social Worker and the ethical mediations. Diving into the details of Social Worker Professional day by day was challenging and satisfying because we unveiled a rich field of mediation ethics that, despite everyday challenges of institutional work, it opens paths and points out possibilities of interventions that aim to guarantee the human rights of users, intending an ethical and political exercise towards emancipatory values signed in the professional Code of Ethics